ASSISTANCE IN THE PREPARATION OF THE OPERATIONAL CURRICULUM FOR MADRASAH IBTIDAIYAH ON SUMBERGEMPOL DISTRICT IN 2024 - Waluyo, Amien Tri (STAI Ma'had Aly Al-Hikam Malang, 2024)
The purpose of this mentoring is to facilitate knowledge and direct practice in the preparation of the Madrasah Operational Curriculum (KOM) in elementary madrasas in Sumbergempol District and ultimately there is an increase in knowledge and skills after carrying out this activity. This research activity in the form of community service research was carried out by the author and supervisor of the Sumbergempol District madrasah which was carried out from July 27 to August 16, 2024 with the target of assistance being 10 Elementary Madrasahs in Sumbergempol District, Tulungagung Regency with a total of 80 participants. The stages in this community service activity consist of the preparation, socialization, mentoring and evaluation stages. This training activity showed results in an increase in the understanding and skills of participants regarding the preparation of KOM which is proof that the entire material provided was successfully understood well by most of the training participants. Mastery of the training material can be seen from the increase in the pre-test and post-test given, where the average pre-test score was 65, increasing in the post-test to 95. In terms of psychomotor abilities, the increase can be proven from the success of the participants in compiling their respective Madrasah Operational Curriculum (KOM) which will later be used in their Madrasah, and their opinions about this activity show real benefits by producing a product in the form of a Madrasah Operational Curriculum (KOM).